Enhancing the quality of life of senior tourists: a theoretical perspective. Issue 4 (2nd October 2021) - Kim, Hyelin (Lina); Sirgy, M. Joseph; Uysal, Muzaffer; Kim, Sung-Eun
ABSTRACT: The goal of this paper is to develop a theoretical perspective to better understand senior tourist behaviour. The perspective is guided by concepts from research on senior tourism, goal theory of leisure travel satisfaction, and socio-emotional selectivity theory. It examines four central principles: (1) selecting leisure travel goals that have high levels of positive valence, (2) selecting leisure travel goals that are very likely to be attained, (3) engaging in actions that would implement leisure travel goals, and (4) engaging in actions that would allow tourists to experience goal attainment. We describe these theoretical principles and sub-principles in relation to senior tourists to build a research agenda to encourage future research.